A study of germination and flowering in Cichorium intybus. L - Minnaar, Hugo Roelof (Rhodes University, Faculty of Science, Botany Department, 1985)
Chicory (Cichorium intybus L) is a deep rooted biennial (or weakly perennial) composite that is grown as an annual in South Africa for its parsnip-like root. In its wild state the plant is a perennial with thin fibrous roots, but, through selection and propagation, cultivars with large, fleshy roots have been developed. From a purely horticultural standpoint, chicory is of interest as a pot-herb, a salad plant and as a root (Bailey, 1942) . As a root, the chicory plant represents an important article of commerce. In South Africa, the plants are grown virtually exclusively for their roots which, after drying, roasting and grinding, are used as an additive to, or substitute for, coffee (Introduction p. 11)
Keywords: Chicory -- South Africa; Germination; Seeds -- Development; Plants -- Flowering of